Friendship As Networking: Youth and Transition to Meaningful Work - Wenty Marina Minza; Arum Febriani; Angelina Shiva Hany; Atikah Hana Hanifah; Octiva Fairuz Izdihar kusharyanti; Fransiska Widianingtyas (Faculty of Psychology, Universitas Gadjah Mada, 2026)
Youth face significant obstacles as they transition from education to work, as job seeking has become more complex. Friendship and networking are considered important resources that acilitate youth entry into a meaningful job market. This study investigates how youth (re)construct the boundaries of friendship and networking. It also examines the ways in which friendship and etworking can smooth the transition from education to meaningful work: work that fulfills the workers’ rights and provides opportunities to grow. Employing a short-term ethnographic approach, this study involved 20 youth aged 20-23 years who met one of two criteria: final semester students who were about to graduate or had just graduated and were actively seeking employment, or workers who had graduated within the last year. Data were collected through observation and in-depth interviews, with photographic documentation capturing participants’ behaviors and social interactions, and interviews eliciting their perspectives, reasoning, and lived experiences of navigating the transition from education to work. The results show that friendship and networking are defined by three relational aspects: self-disclosure, closeness, and support. These aspects determine the extent to which relationship is considered friendship or networking, depending on the intensity of those aspects of the relationship. The study highlights that in the context of the education-to-work transition, friendships and networks often intertwine. This study suggests that promoting early networking may support a smoother transition toward meaningful work.